MANAGEMENT OF PRODUCTION PROCESSES OF AN AGRICULTURAL ENTERPRISE IN THE CONDITIONS OF RENEWABLE ENERGY DEVELOPMENT - Smetan, Denys (Current Problems of Sustainable Development, 2026)
Agriculture is a sector of the economy that consumes a large number of various resources. Energy resources play a significant role in this. In addition, the sustainable development and functioning of agricultural enterprises require a continuous energy supply. Agricultural buildings, greenhouses, feed storage facilities and many other facilities consume a huge amount of energy. Lighting, heating and various technological processes at different stages of production require a constant energy supply. Although agro-industrial enterprises are not considered to have a continuous production cycle that requires a continuous energy supply, the lack of such a supply negatively affects their efficiency. In recent decades, many farms have tried to replace traditional energy sources with alternative energy sources at certain stages of production. This  is due to both the desire for energy independence and the profitable use of available resources. The economic feasibility of using alternative energy sources depends on avoiding fuel delivery costs and independence from centralized energy networks. In this context, renewable energy is of particular importance. In Ukraine, the renewable energy market is underdeveloped due to the traditional dependence on fossil fuels and nuclear power. However, renewable energy can be particularly useful in remote regions of the country, as it simplifies logistics and contributes to economic development. The scale of losses in agriculture depends significantly on the type and size of the enterprise. Large livestock and poultry farms can be compared to industrial companies in terms of the level of electricity consumption and the complexity of their electrical systems. In addition, the deterioration of the quality of electricity leads to interruptions in the supply of agricultural consumers. Modern environmental conditions and global processes are increasingly stimulating the transition to renewable energy sources to reduce environmental impact and promote sustainable economic development of both individual countries and the global community. In this context, renewable energy is gaining particular importance. In Ukraine, the renewable energy market is underdeveloped due to the traditional focus on fossil and nuclear fuels. At the same time, renewable energy can be especially relevant in remote regions of the country, as it simplifies logistics and promotes economic development. Given the technical complexity and the need for significant initial investments, successful management of a startup in the field of renewable energy requires a comprehensive understanding of both the specifics of the industry and innovative business planning and strategic management strategies. The application of best management practices and the willingness to adapt to market changes are crucial for success in this rapidly developing sector.
Keywords: renewable energy; agricultural enterprises; energy sources; economy